Axillary web syndrome after treatment for breast cancer: An exploration of imaging evidence of fascial changes and its relationship to clinical variables - Paulssen, Kyle Joseph Catharina (Department of Human Biology, 2020)
Breast cancer is the most commonly diagnosed cancer in women and surgery remains the primary treatment. Evaluation of tumour spread is done by axillary lymph node assessment by surgical excision. Such invasive treatments, in conjunction with adjuvant therapies such as chemotherapy, radiotherapy and hormonal therapy, may alter patient healing patterns giving rise to complications such as axillary web syndrome (AWS). AWS presents as a puckering web of axillary skin overlying a cord of tissue that tightens with shoulder abduction. It is painful, limits shoulder range of movement (ROM) and reduces the quality of life of the patients. The syndrome is elusive, does not occur in everyone and is thought to be self-limiting in nature with spontaneous cord resolution. Evidence, however, is pointing towards long-term morbidity in some patients. The cord itself has been hypothesised to be lymphatic or vascular in origin and damage during axillary surgery gives rise to the structure. Anatomically, the vascular structures are bound by the connective tissue network of fascia. The adhesive and puckering appearance of the cord on clinical examination and in limited biopsy studies could imply a possible role of damaged fascia in the syndrome. The fascia, as a three-dimensional body-wide network, has been shown to be a functional unit with the musculoskeletal system and is important in coordinating movement. Furthermore, the fascia contains numerous receptors imperative for proprioceptive and nociceptive functioning. The fibroblast cells and fibres that it comprises are involved in tissue healing and scar tissue formation. Chronic inflammation upon fascial damage can lead to tissue adhesions and fibrosis, rendering a non-functional scar. Ultrasonography (US) has been able to visualise fascial differences and has been used to examine fascial abnormalities including scars and adhesions. Physiotherapy treatment has been shown to aid in remobilising scar tissue and in being able to help improve morbidity in AWS patients. The authors therefore hypothesised that damaged fascia contributes to the symptomology of AWS. The present study set out to evaluate whether altered fascia plays a role in the syndrome using fascial explanations for risk factors in the AWS literature and US in patients with AWS to observe anatomical changes. Furthermore, the authors hypothesised that myofascial physiotherapy could aid in cord resolution and symptom improvement and that it would reflect in fascial changes on US. The current descriptive, observational, pilot, proof-of-concept case-series study focused on fascial changes before and after myofascial release physiotherapy in women presenting with AWS following breast cancer treatment (n = 11). At the time points, US in the area of interest (the axilla) and MRI scans of a single patient were done pre-physiotherapy. Furthermore, patient variables of ROM, pain and disability using the SPADI questionnaire, and quality of life using the FACT-B questionnaire, were evaluated to relate to any fascial differences between affected and unaffected arms on US and compared to findings after physiotherapy to determine trends. To observe fascial continuity, alignment of US scans was attempted. The results from the case studies and overall trends indicated thickened fascia, reduced continuity, decreased gliding potential and increased adherence between the different fascial layers on US in the majority of patients on the affected arm in the area of interest suggesting that they are changes resulting from the treatment. The findings related to the external cord appearance. On MRI, a fibrous band of tissue was observed connecting to muscles and skin. The findings were found to descriptively show a trend with reduced ROM and increased SPADI scores. No descriptive relationship with FACT-B was noted. Several patients (n = 6) continued with physiotherapy for six treatments. The treatment proved beneficial for all patients, who improved on ROM and SPADI scores. However, not all their symptoms were completely resolved. The findings corroborate observations on US showing improved gliding, more regular and organised fascia, and less adhesions post-physiotherapy. Cord resolution or reduction occurred in half of the patients. Risk factors for AWS as identified in the literature and related to the patients, such as more invasive treatments and (neo)adjuvant therapies, were explained to cause more fibrosis and possibly contributed to the symptoms seen but could not be verified in the study due to the small, varied sample. Furthermore, due to the difficulty of finding suitable patients and the low sample size, the current study could not statistically corroborate many correlations and hence was limited to descriptive trend description. Using the fascial literature, restricted fascia and adhesions could be explained to lead to biomechanical limitations, explaining reduced ROM and nociceptor activation as seen in pain reported in the study. A fibrosed vessel damaged during axillary surgery as well as surrounding fascial changes, which occurred as the result of the healing response, could explain the varying appearances of the cord. The author concluded that the trends seen suggest a link for morbidity resulting from fascial damage and adds weight to the evidence of fascial involvement in AWS. Wider fascial involvement on US and MRI descriptively related to the presence of cording, limited shoulder ROM and pain before and improvements and changes in the domains after physiotherapy, supported the hypotheses. The present study highlighted that myofascial release can be beneficial for patients suffering from AWS and suggests that US may be a feasible outcome measure to aid in evaluating fascia and fibrosis subsequent to physiotherapy, guide it and determine its efficacy. Furthermore, risk factors need to be identified to implement an early warning system for the sequelae of breast cancer so that patients at risk are identified timeously and receive the help they need to minimise the effect of the syndrome on their wellbeing in order to improve their quality of life.